2013
DOI: 10.2527/jas.2011-4286
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of dietary ractopamine HCl and L-carnitine on finishing pigs: I. Growth performance1,2

Abstract: A total of 2,152 pigs (C22 × 336 PIC) were used in 4 experiments to determine the interactive effects of dietary l-carnitine and ractopamine HCl (RAC) on finishing pig growth performance. All trials were arranged as factorial arrangements with main effects of l-carnitine (0, 25, or 50 mg/kg in Exp. 1 and 2 and 0 or 50 mg/kg in Exp. 3 and 4) and RAC (0, 5, or 10 mg/kg in Exp. 1 and 0 or 10 mg/kg in Exp. 2, 3, and 4). Dietary carnitine was fed from 38 to 109 kg (Exp. 1 and 3) or for the last 4 or 3 wk before sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
1
13
1
1
Order By: Relevance
“…Present results are in agreements with the report of James et al (2013) who observed 3.1% and 4.1% increase in ADG and FCE in finisher pigs by dietary inclusion of 50 mg of L-carnitine/kg compared to non-supplemented group. In contrary to present results, James et al (2014) observed no effect on ADG and gain: feed ratio by feeding L-carnitine at 50 mg/kg for pigs weighing 36 to 86 kg, respectively. The results revealed no differences (P>0.05) between treatments T1, T2 and T3 in related to weight gain and average daily gain for finisher pigs (Table 2).…”
Section: Body Weight Gain and Feed Utilization Efficiencycontrasting
confidence: 99%
“…Present results are in agreements with the report of James et al (2013) who observed 3.1% and 4.1% increase in ADG and FCE in finisher pigs by dietary inclusion of 50 mg of L-carnitine/kg compared to non-supplemented group. In contrary to present results, James et al (2014) observed no effect on ADG and gain: feed ratio by feeding L-carnitine at 50 mg/kg for pigs weighing 36 to 86 kg, respectively. The results revealed no differences (P>0.05) between treatments T1, T2 and T3 in related to weight gain and average daily gain for finisher pigs (Table 2).…”
Section: Body Weight Gain and Feed Utilization Efficiencycontrasting
confidence: 99%
“…Several studies have shown that pigs fed 10 mg/kg RAC have 6 to 16% less fat at the 10th rib than pigs not fed RAC (Apple et al, 2004a(Apple et al, , 2008Carr et al, 2005b). One item potentially explaining the variability in our results could be the difference in level of feed (energy) intake between the studies conducted with 2 pigs per pen compared with the pigs housed in the commercial facility (James et al, 2013). Pigs in Exp.…”
Section: Carcass Measurementsmentioning
confidence: 76%
“…The pigs used in these experiments were part of a larger project (James et al, 2013) conducted to evaluate the interactive effects of dietary L-carnitine and RAC (Elanco Animal Health, Greenfield, IN) on growth performance of growing-finishing pigs. All pigs used in these experiments were progeny of C22 females × 336 boars (PIC, USA, Hendersonville, TN).…”
Section: Generalmentioning
confidence: 99%
“…The inconsistent results for the use of L-carnitine can be attributed to several causes, such as the sanitary status; the age of the animals; and environmental, genetic, and nutritional factors (JAMES et al, 2013;RINCKER et al, 2003). In the present study, the dose of 50 mg L-carnitine kg -1 of feed was within the values commonly employed in experiments and commercial farming (HARMEYER, 2003;OWEN et al, 2001;RINGSEIS et al, 2018) and proved effective under the conditions of this test.…”
Section: Parametersmentioning
confidence: 46%
“…In biochemical processes, L-carnitine forms esters from long-chain fatty acids catalyzed by the enzyme carnitine palmitoyltransferase I (SASEENDRAN et al, 2017), which is able to penetrate the mitochondrial membrane (HEO et al, 2000;JAMES et al, 2013). These esters are then cleaved again through the action of carnitine palmitoyltransferase II and released within the mitochondria to be used for energy production (HEO et al, 2000).…”
Section: Parametersmentioning
confidence: 99%